Wettability of Amino Acid-Functionalized Psma Electrospun Fibers for the Modulated Release of Active Agents and Its Effect on Their Bioactivity - Hamm-Hahn, L (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The ideal treatment for chronic wounds is based on the use of bioactive dressings capable of releasing active agents. However, the control of the rate at which these active agents are released is still a challenge. Bioactive polymeric fiber mats of poly(styrene-co-maleic anhydride) [PSMA] functionalized with amino acids of different hydropathic indices and L-glutamine, L-phenylalanine and L-tyrosine levels allowed obtaining derivatives of the copolymers named PSMA@Gln, PSMA@Phe and PSMA@Tyr, respectively, with the aim of modulating the wettability of the mats. The bioactive characteristics of mats were obtained by the incorporation of the active agents Calendula officinalis (Cal) and silver nanoparticles (AgNPs). A higher wettability for PSMA@Gln was observed, which is in accordance with the hydropathic index value of the amino acid. However, the release of AgNPs was higher for PSMA and more controlled for functionalized PSMA (PSMAf), while the release curves of Cal did not show behavior related to the wettability of the mats due to the apolar character of the active agent. Finally, the differences in the wettability of the mats also affected their bioactivity, which was evaluated in bacterial cultures of Staphylococcus aureus ATCC 25923 and methicillin-resistant Staphylococcus aureus ATCC 33592, an NIH/3T3 fibroblast cell line and red blood cells. © 2023 by the authors.